The Effect of Connected Mathematics Project Model and Learning Cycle 5e Model on Mathematics Learning Outcomes - Rahmadina, Shiva Nur Aulia; Slamet, Slamet (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
This research is motivated by real problems, namely that there are still many students who get low math learning outcomes because they use learning models that are not in accordance with student needs. This study aims: 1) to determine the mathematics learning outcomes in classes that apply the CMP learning model, 2) to determine the mathematics learning outcomes in classes that apply the LC5E learning model, 3) to determine the effect of the difference in mathematics learning outcomes between classes that apply the CMP learning model and classes that apply the LC5E learning model at SMA Negeri 109 Jakarta academic year 2023/2024. This research used a quantitative approach with the Quasi Experimental Design method. The sample consisted of two XI classes taken randomly, with the experimental class applying the CMP model and the control class applying the LC5E model, each totalling 40 students. The results showed that there was a different effect of math learning outcomes between the two learning models. The average math learning outcomes in the experimental class (CMP) reached 88,90, while in the control class (LC5E) the average was 82,63. Hypothesis testing using the Independent Samples T-Test test shows a Sig. value of 0.032 , which means there is a different effect between the learning outcomes of the two groups. Therefore, the CMP learning model is more effective in improving students' mathematics learning outcomes than the LC5E model, especially if the instrument used is Higher Order Thinking Skill (HOTS) questions.